Early childhood caries and their association with serum iron, serum ferritin, serum albumin, and Vitamin D - Vasundhara Megha; Jeevendra Nath Shukla; Rajat Kumar Singh; Chitrita Gupta Mukherjee; Siddharth Anand; Aparna Singh (Journal of Family Medicine and Primary Care)
Aim: The present study aimed to correlate the association between serum iron, serum ferritin, serum albumin, and Vitamin D with early childhood caries (ECC). Materials and Methods: This study was a single-blinded randomized control trial. A total of 200 children aged between 3–6 years were screened for ECC, according to the AAPD guidelines. Out of 200 children, a total of 177 children fulfilled the inclusion criteria. They were divided into two groups: Group 1 consisted of 99 children with ECC and Group 2 (control group) with 78 children. The decayed, extracted because of caries, and filled primary teeth (deft) index were recorded from these children. Blood samples (approximately 2 ml) were collected by an expert nurse in the morning to determine serum levels of iron, ferritin, albumin, and Vitamin D. The data was statistically analyzed using the Mann–Whitney U test, and P value 0.05 was considered significant. Results: The mean deft score was 4.83 (±3.54). The mean value of serum iron was 64.66 (±8.35) μg/dl, serum albumin 3.88 (±0.57) gm/dl, and serum ferritin 29.19 (±42.11) ng/ml in ECC children, whereas mean serum iron was 67.78 (±6.17), serum albumin 3.82 (±0.62) gm/dl, and serum ferritin 26.38 (±23.04) ng/ml in caries-free children. Statistically, no significant relationship was observed between serum iron (P = 0.066), serum albumin (P = 0.448), and serum ferritin (P = 0.192) with ECC. The mean value of Vitamin D was 17.44 (±7.59) ng/ml in ECC children and 35.9 (±9.56) in caries-free children who were significantly low in comparison with the non-ECC subjects (P < 0.0001). Conclusion: The present study suggests no relationship between serum iron, serum albumin, and serum ferritin with ECC, whereas Vitamin D had an inverse relationship with ECC. Clinical Significance: This study sets a benchmark for the dental fraternity and other health specialists to analyze serum iron, serum ferritin, serum albumin, and Vitamin D levels, while generally treating pediatric patients with or without dental caries. Oral health education campaigns should be conducted for public awareness about the importance of iron, ferritin, albumin, and Vitamin D.